ADAKAH PERILAKU OPORTUNISTIK DALAM APLIKASI AGENCY THEORY DI SEKTOR PUBLIK? - Nurul Latifah Pancawardani (STIE Pelita Nusantara Semarang, 2010)
Implementation of regional autonomy in Indonesia based on Law 22/1999 and Law 25/1999. The implementation of regional autonomy opportunities application research agency theory in public budgeting. The legislature is a principal party to the executive but also as agent for Voters. The occurrence of asymmetry of information between the executive and legislative branches to be not of much value when the legislature uses discretionary powerin budgeting. Agents have more information about the actual performance, motivation, and purpose, potentially creating moral hazard and adverse selection. Principals themselves must pay (costs) to monitor agency performance and determine the structure of incentives andefficient monitoring. The existence of information asymmetry between executive-legislative and legislative-voter lead the opening of space for the occurrence of opportunistic behavior in the budgeting process.